Elucidation of physicochemical properties of polysaccharides extracted from Cordyceps militaris fruiting bodies with different drying treatments and their effects on ulcerative colitis in zebrafish - Wei, Yin; Du, Xiao; Guo, Yangbian; Chang, Mingchang; Deng, Bing; Liu, Jingyu; Cao, Jinling (Frontiers in Nutrition, 2022)
Dry fruiting bodies of Cordyceps militaris (CMF) have been widely used in folk tonic foods and traditional herbal medicine in East Asia. Drying treatment serves as the last step in CMF industrial processes. In this work, the physicochemical properties of polysaccharides from C. militaris fruiting bodies (CMFPs) with hot air drying (HD), far-infrared radiation drying (ID) and vacuum freeze-drying (FD) treatments were analyzed, and their effects on ulcerative colitis (UC) were further investigated in oxazolone-induced zebrafish. The results showed that physicochemical properties of CMFP-H, CMFP-I and CMFP-F were obvious different. CMFPs could repair the intestinal mucosal barrier, inhibit ROS generation and the activities of MDA and MPO, and improve the activities of SOD, CAT, ACP, AKP and LZM. Further detection indicated that CMFPs could better improve UC via activating the MyD88/NF-κB signaling pathway in vivo. However, CMFP-H, CMFP-F and CMFP-I exhibited diverse regulation effects on specific immune-related enzymes and cytokines. The data would be helpful for finding practical and rapid drying methods for macro-fungi and further exploring CMFPs as functional food ingredients or complementary medicines for the treatments of UC.